Guidewire Ablation within the Coronary Venous System for Epicardial or Intramural Ventricular Arrhythmia: A Preclinical Study of Biophysical Characterization - Fengqi Xuan; Zhongyin Zuo; Jie Zhang; Shibei Zhang; Zichen Liu; Yunfan Meng; Kuo Sun; Yaling Han; Ming Liang; Zulu Wang (Cardiology Research and Practice)
Background. Catheter ablation failure poses a clinical challenge for epicardial or intramural ventricular arrhythmia (VA); however, guidewire ablation within the coronary venous system (CVS) may be effective and safe for targeting VAs. Methods. The ex vivo phase included four steps. In step 1, the steam pop incidence rates during guidewire ablation at power settings of 5, 10, 15, 20, and 25 W were analyzed using 10 mm- and 20 mm-tip guidewires. In step 2, guidewire ablation was performed for application durations of 10, 20, 30, 40, 50, 60, and 90 s, and the lesion size was measured. In step 3, the effects of saline infusion (0, 1, 2, 3, and 4 mL/min) on lesion dimensions and steam pop formation were examined. In step 4, an orthogonal array was constructed to obtain the optimal guidewire ablation parameters. In the in vivo phase, guidewire ablation within the CVS was performed in three dogs, and the lesion features in 10 days after ablation were observed. Results. In step 1, the steam pop incidence rates at 5, 10, 15, 20, and 25 W were 0%, 0%, 12.5%, 62.5%, and 100% using the 10 mm-tip guidewires and 0%, 0%, 0%, 25%, and 75% using the 20 mm-tip guidewires, respectively. In step 2, we found that the lesion areas increased with an increase in the ablation duration (the maximum lesion diameters at 30, 60, and 90 s were 4.9 ± 0.4, 7.0 ± 0.8, and 9.2 ± 0.7 mm in the 10 mm group and 3.2 ± 0.5, 4.5 ± 0.4, and 5.3 ± 0.7 mm in the 20 mm-tip group, respectively). In step 3, we observed that saline infusion was negatively correlated with ablation lesions but had a lower risk of steam pop. The optimal parameters for the 20 mm-tip guidewire ablation were 15 W, 50 s, and 2 mL/min or 20 W, 70 s, and 2 mL/min. In the in vivo phase, effective ablation lesions with maximum and minimum diameters of 3.2 ± 0.3 and 2.8 ± 0.5 mm, respectively, were created by the guidewires during the 10-day observation period after ablation. Conclusion. This novel radiofrequency guidewire ablation technique can feasibly create effective lesions within the CVS, which may improve the efficacy of catheter ablation for challenging epicardial or intramural VA.